Trends in access to health services and financial protection in China between 2003 and 2011: a cross-sectional study - Meng, Qun; Xu, Ling; Zhang, Yaoguang; Qian, Juncheng; Cai, Min; Xin, Ying; Gao, Jun; Xu, Ke; Boerma, J Ties; Barber, Sarah L (The Lancet (British edition), 2012)
In the past decade, the Government of China initiated health-care reforms to achieve universal access to health care by 2020. We assessed trends in health-care access and financial protection between 2003, and 2011, nationwide. We used data from the 2003, 2008, and 2011 National Health Services Survey (NHSS), which used multistage stratified cluster sampling to select 94 of 2859 counties from China's 31 provinces and municipalities. The 2011 survey was done with a subset of the NHSS sampling frame to monitor key indicators after the national health-care reforms were announced in 2009. Three sets of indicators were chosen to measure trends in access to coverage, health-care activities, and financial protection. Data were disaggregated by urban or rural residence and by three geographical regions: east, central, and west, and by household income. We examined change in equity across and within regions. The number of households interviewed was 57 023 in 2003, 56 456 in 2008, and 18 822 in 2011. Response rates were 98·3%, 95·0%, and 95·5%, respectively. The number of individuals interviewed was 193 689 in 2003, 177 501 in 2008, and 59 835 in 2011. Between 2003 and 2011, insurance coverage increased from 29·7% (57 526 of 193 689) to 95·7% (57 262 of 59 835, p<0·0001). The average share of inpatient costs reimbursed from insurance increased from 14·4 (13·7–15·1) in 2003 to 46·9 (44·7–49·1) in 2011 (p<0·0001). Hospital delivery rates averaged 95·8% (1219 of 1272) in 2011. Hospital admissions increased 2·5 times to 8·8% (5288 of 59 835, p<0·0001) in 2011 from 3·6% (6981 of 193 689) in 2003. 12·9% of households (2425 of 18 800) had catastrophic health expenses in 2011. Caesarean section rates increased from 19·2% (736 of 3835) to 36·3% (443 of 1221, p<0·0001) between 2003 and 2011. Remarkable increases in insurance coverage and inpatient reimbursement were accompanied by increased use and coverage of health care. Important advances have been made in achieving equal access to services and insurance coverage across and within regions. However, these increases have not been accompanied by reductions in catastrophic health expenses. With the achievement of basic health-services coverage, future challenges include stronger risk protection, and greater efficiency and quality of care. None.